(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Temperature has great influence on mechanical, electrical and chemical processes that occur in transition layer of sliding contact. The aim of the research is creating a three-dimensional finite-element model for calculating time dependent thermal process in sliding electrical microcontact.The article starts with the description of the contact element representing a discrete microcontact and physics in it. Then the authors suggest use modern simulation software COMSOL Multyphisics for modeling.The developed 3D-model uses modules of electric currents, heat transfer in solids, and electromagnetic heat source for computing. For each module the assumptions, the initial and boundary conditions are made. The outcomes of modeling are the transient processes of average overheat in the elements of contact-details surface layers. The transient processes depend on geometric size of the microcontact (size of contact element, height of surface elements, thickness of oxide films, and overlap), contact-details physical properties (density, electrical conductance, thermal conductivity, and heat capacity), external influences (electrical current and friction heat), and temperatures of the neighbor elements.The results of the research will be used in the numerical simulation model of sliding electrical contact.